“A LOT OF THEM ARE GOOD BUGGERS”: THE AFRICAN “FOREIGNER” AS SOUTH AFRICA’S DISCURSIVE OTHER - Jearey-Graham, Nicola; Böhmke, Werner (PINS-Psychology in Society, 2025)
Levels of xenophobia in South Africa have risen precipitously since the early 1990s, but this phenomenon does not appear to have been researched rigorously within psychology. This exploratory study looks at how seven South African “citizens”1 talk about African “foreigners”¹ in South Africa, using a synthetic discursive lens which analyses the Self-Other relationships which are constructed. Subject positioning, ideological dilemmas and rhetorical work are used as analytical tools. Analysis reveals that a discursive relationship of common humanity leads to compassionate inclusivity, but the positioning of African “foreigners” as inferior/serviceable or threatening justifies their exploitation or exclusion, whilst enabling participants to “dodge the identity of prejudice”. National identity was constructed as one of fragile superiority over other African countries, resulting in a perceived need to protect the nation from outsiders. Participants took up familial identity positions, and this discursive mobilisation of the metaphor of “family” mirrors ideological models of the function of the state as an imaginary agency responsible for the protection and care of the citizenry.